2005
DOI: 10.4049/jimmunol.174.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ca2+ Signaling by Na+/Ca2+ Exchangers in Mast Cells

Abstract: Mast cells rely on Ca2+ signaling to initiate activation programs leading to release of proinflammatory mediators. The interplay between Ca2+ release from internal stores and Ca2+ entry through store-operated Ca2+ channels has been extensively studied. Using rat basophilic leukemia (RBL) mast cells and murine bone marrow-derived mast cells, we examine the role of Na+/Ca2+ exchangers. Calcium imaging experiments and patch clamp current recordings revealed both K+-independent and K+-dependent components of Na+/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…A similar cross-talk has been proposed to exist between CRAC channels and the plasma membrane Na ϩ /Ca 2ϩ exchanger (NCX) in mast cells (34). Nevertheless, the relative contribution of these systems to the control of local [Ca 2ϩ ] varies significantly with the experimental conditions used, the time window analyzed and the cell type under study.…”
Section: Discussionmentioning
confidence: 77%
“…A similar cross-talk has been proposed to exist between CRAC channels and the plasma membrane Na ϩ /Ca 2ϩ exchanger (NCX) in mast cells (34). Nevertheless, the relative contribution of these systems to the control of local [Ca 2ϩ ] varies significantly with the experimental conditions used, the time window analyzed and the cell type under study.…”
Section: Discussionmentioning
confidence: 77%
“…This, therefore, explains the role of the exchanger not only in E-C coupling, but also in the control of the neurosecretion processes (42,43,133). Furthermore, the Na 2ϩ /Ca 2ϩ exchanger, working in the extrusion mode, has being recently implicated in the modulation of Ca 2ϩ signal in mast cells (7). Finally, there are numerous reports that link the Na ϩ /Ca 2ϩ exchanger with many pathophysiological syndromes including heart arrhythmias, all salt-dependent hypertension, reperfusion injury, and cardiac ischemia, among others (34,35,40,43,173,185,193,238,241,255).…”
Section: Discovery Evolution Of the Field In Time And Physiologimentioning
confidence: 99%
“…Interestingly, preliminary studies in murine macrophages [14] and human basophils [15] have suggested the presence of NCX in immune cells. NCX activities have also been reported in human lymphocytes [16], neutrophils [17], and rat mast cells [18,19] investigated using pharmacological agents. In these cells, NCX may contribute either to the extrusion of Ca 21 after Ca 21 -spiking events or to the increase in [Ca 21 ] i during cell activation.…”
Section: Introductionmentioning
confidence: 99%